A new model for estimating peak oxygen uptake based on postexercise measurements in swimming - Chaverri, D.; Schuller, T.; Iglesias, X.; Hoffmann, U.; Rodriguez, F. A. (International Journal of Sports Physiology and Performance, 2016)
Purpose: Assessing cardiopulmonary function during swimming is a complex and cumbersome procedure. Backward extrapolation is often used to predict peak oxygen uptake (VO2peak) during unimpeded swimming, but error can derive from a delay at the onset of VO2 recovery. The authors assessed the validity of a mathematical model based on heart rate (HR) and postexercise VO2 kinetics for the estimation of VO2peak during exercise.